Impact of glycogen storage disease type I on adult daily life: a survey - Garbade, Sven; Ederer, Viviane; Burgard, Peter; Wendel, Udo; Spiekerkötter, Ute; Haas, Dorothea; Grünert, Sarah (Orphanet journal of rare diseases, 2021)
Glycogen storage disease type I (GSD I) is a rare autosomal recessive disorder of carbohydate metabolism characterized by recurrent hypoglycaemia and hepatomegaly. Management of GSD I is demanding and comprises a diet with defined carbohydrate intake and the use of complex carbohydrates, nocturnal tube feeding or night-time uncooked cornstarch intake, regular blood glucose monitoring and the handling of emergency situations. With improved treatment, most patients nowadays survive into adulthood. Little research has been performed on the impact of GSD I on daily life, especially in adult patients.
Gesehen am 21.10.2021